1996
DOI: 10.1164/ajrccm.154.1.8680687
|View full text |Cite
|
Sign up to set email alerts
|

Greater ozone-induced inflammatory responses in subjects with asthma.

Abstract: In order to test the hypothesis that ozone (O3)-induced changes in lung function and respiratory tract injury/inflammation are greater in subjects with asthma than in normal subjects, we exposed 18 asthmatic subjects, on separate days, to O3 (0.2 ppm) and filtered air for 4 h during exercise. Symptom questionnaires were administered before and after exposure, and pulmonary function tests (FEV1, FVC, and specific airway resistance [SRaw]) were performed before, during, and immediately after each exposure. Fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
95
3
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(109 citation statements)
references
References 20 publications
10
95
3
1
Order By: Relevance
“…Prior studies have yielded mixed results 14, 15, 16, 17, 18. In a recent study, positive associations of short‐term exposure to fine particulate matter (diameter ≤2.5 μm [PM 2.5 ]), black carbon (BC), and nitrogen oxides (NO x ) with myeloperoxidase were found in a group of potentially genetically susceptible participants 14…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have yielded mixed results 14, 15, 16, 17, 18. In a recent study, positive associations of short‐term exposure to fine particulate matter (diameter ≤2.5 μm [PM 2.5 ]), black carbon (BC), and nitrogen oxides (NO x ) with myeloperoxidase were found in a group of potentially genetically susceptible participants 14…”
Section: Introductionmentioning
confidence: 99%
“…In clinical exposures of asthmatics, short exposure to air pollution produces increased airway reactivity. Thresholds in sulfur dioxide-induced bronchoconstriction were lower in asthmatics (10), and ozone-induced lung function change and respiratory tract injury and inflammation were more prominent in asthmatics (11).…”
mentioning
confidence: 97%
“…Bronchoscopy was first used by Seltzer and colleagues (18) to detect airway inflammation in response to 03 exposure. Since then, bronchoscopy has allowed investigators to characterize the nature of the airway inflammatory response to single and repeated exposures to 03 in healthy, allergic, and asthmatic subjects (19)(20)(21)(22). It has been used to study the effects of exposure to many pollutants in addition to 03, including NO2 (23-25), SO2, (26), acid aerosols (27)(28)(29), and diesel exhaust (30).…”
Section: Experimental Design and Methodsmentioning
confidence: 99%
“…Two recent studies suggested that mild asthmatics may experience a neutrophilic airway inflammatory response to 03 exposure that is more intense than in healthy subjects (22,93). Recent studies have also shown that, in asthmatics, 03 exposures at concentrations sufficient to induce an airway inflammatory response increase responsiveness to a subsequent allergen challenge (94).…”
Section: Asthmamentioning
confidence: 99%